2017
DOI: 10.1149/2.1291704jes
|View full text |Cite
|
Sign up to set email alerts
|

Cathode Performance of Co-Doped Li2O with Specific Capacity (400 mAh/g) Enhanced by Vinylene Carbonate

Abstract: A Co-doped Li2O (CDL) was synthesized using a planetary ball mill and examined as a cathode material for lithium-ion batteries. When vinylene carbonate, which is often employed as an additive in an electrolyte, was used not only as an additive in the electrolyte but also as a treatment agent for CDL, the specific capacity of CDL was greatly enhanced and the charge–discharge cycles with specific charging and discharging capacities of 400 mAh/g could be repeated for more than 50 times. Co K-edge XANES spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…In addition, the surface modification of CoDL by vinylene carbonate or fluoroethylene carbonate shows excellent capacity improvement from 270 to 450 mA h g À1 while retaining its cyclability. [50][51][52] Since TMDLs are basic and reactive with the electrolyte to decompose, such surface modification is also effective for enhancement of cathode performances.…”
Section: Effect Of Ni-doping To Lithium Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the surface modification of CoDL by vinylene carbonate or fluoroethylene carbonate shows excellent capacity improvement from 270 to 450 mA h g À1 while retaining its cyclability. [50][51][52] Since TMDLs are basic and reactive with the electrolyte to decompose, such surface modification is also effective for enhancement of cathode performances.…”
Section: Effect Of Ni-doping To Lithium Oxidementioning
confidence: 99%
“…Contrarily, metal doping of Li 2 O effectively utilizes oxygen redox. Previous studies have reported that 5-10 mol% TM consisting of Fe, 46 Co, [47][48][49][50][51][52] Cu, 53 Rh, 47 and Ir 47 are substitutionally introduced to the cationic site of Li 2 O. The transition metal-doped Li 2 O (TMDL) cathodes exhibit a reversible solid-state oxygen redox reaction, along with a TM dopant redox reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Co-substituted Li 2 O shows a specific capacity of approximately 450 mA h g –1 . 4 9 It has been reported that Co-substituted Li 2 O follows eq 1 during the charge–discharge process. However, Co-substituted Li 2 O decomposes according to eq 2 when overcharged.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the capacity of commercial cathodes was not critically affected by the electrolyte additive, but the effect of the additive significantly enhanced the rate capability, cyclic performance, and efficiency of the cells. By contrast, some lithia-based cathodes showed improved available capacity through the addition of electrolyte additives [28][29] , a fairly unique outcome. In this work, the electrochemical performance of lithia/Li 2 RuO 3 nanocomposites through the addition of TMSB was carefully characterised.…”
mentioning
confidence: 99%
“…However, it is difficult to apply to lithia-based cathodes because a coating process utilising heat-treatment may significantly deteriorate lithia-based cathodes due to the extremely reactive lithia. Whereas, the use of electrolyte additives may be a promising solution to the interfacial problem of lithia-based cathodes [28][29] . The additives dissolve in the decomposed electrolyte during cycling to form a protective layer on the surface of the cathode.…”
mentioning
confidence: 99%